Black Wolf of the Glacier : Alaska's Romeo - Vanasse, Deb (Book collections on Project MUSE., 2013)
When a lonely wolf makes friends with her dog, Shawna's fear turns to love. Based on the true story of Romeo, a wolf who lived near Juneau's Mendenhall Glacier and lost his wolfpack as a young male.